2014
DOI: 10.1111/jdv.12939
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune comorbid diseases associated with lichen planus: a nationwide case–control study

Abstract: Lichen planus is associated with various autoimmune diseases. Further study is required to elucidate the possible underlying mechanisms and roles of autoimmunity in the aetiology of LP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 31 publications
2
24
2
2
Order By: Relevance
“…LP has been associated with a variety of systemic disorders such as alopecia areata, vitiligo, myasthenia gravis, active chronic hepatitis, hypertension, Sjögren syndrome, lupus erythematosus, or thyroid pathology (Alaizari, Al‐Maweri, Al‐Shamiri, Tarakji, & Shugaa‐Addin, ; Barbosa et al, ; Chung et al, ; Kiyani & Shahroz, ; Likar‐Manookin et al, ; Robledo‐Sierra et al, ) Of all the articles included, there are only four, which define part of these alterations as exclusion criteria (Mohsin et al, ; Petrou‐Amerikanou et al, ; Saini et al, ; Van Dis & Parks, ). The remaining studies, with the exception of Al‐Maweri et al () who generically defined “immunologic diseases” as exclusion criteria, do not take into account the possible presence of this type of alterations when forming the study population.…”
Section: Discussionmentioning
confidence: 99%
“…LP has been associated with a variety of systemic disorders such as alopecia areata, vitiligo, myasthenia gravis, active chronic hepatitis, hypertension, Sjögren syndrome, lupus erythematosus, or thyroid pathology (Alaizari, Al‐Maweri, Al‐Shamiri, Tarakji, & Shugaa‐Addin, ; Barbosa et al, ; Chung et al, ; Kiyani & Shahroz, ; Likar‐Manookin et al, ; Robledo‐Sierra et al, ) Of all the articles included, there are only four, which define part of these alterations as exclusion criteria (Mohsin et al, ; Petrou‐Amerikanou et al, ; Saini et al, ; Van Dis & Parks, ). The remaining studies, with the exception of Al‐Maweri et al () who generically defined “immunologic diseases” as exclusion criteria, do not take into account the possible presence of this type of alterations when forming the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact causes of this lichenoid tattoo reaction are not yet identified, based on previous reports, we suggest that this reaction might be due to an autoimmune disease . The mechanism of this tattoo‐stimulated lichenoid reaction can be explained.…”
mentioning
confidence: 67%
“…Embedded dye particles act as antigens, mediating delayed hypersensitivity by simulating a graft‐vs‐host reaction. Abundant infiltrating T cells secreting matrix metal protein 9 and type‐1 cytokines cause epidermal basal cell apoptosis, which is a defining hallmark of the disease microenvironment . Among all of the dye colors, the red pigment, composed of sulfur, silicon, aluminum, chlorine, and mercury, is more prone to induce a lichenoid tattoo reaction.…”
mentioning
confidence: 99%
“…Recently, Chung PI et al [10] reported a significant association with systemic lupus erythematosus, Sjögren's syndrome, dermatomyositis, vitiligo and alopecia areata among patients with LP.…”
Section: Discussionmentioning
confidence: 99%